Comprehensive Medical and Psychological Rehabilitation in War Trauma (clinical case) - Panchenko , O.A.; Kabantseva , A.V.; Zhogina, O.O.; Serdyuk, I.A. (Medicni Perspektivi, 2024)
The purpose of the work was to analyze a clinical case of the course of war trauma and presents the experience of providing comprehensive medical and psychological clinical rehabilitation to a patient who suffered as a result of a terrorist attack. Patient D., 65 years old, sustained a mine-blast injury (MBI) to the right upper limb extremity during shelling. The optimal restoration of the functions of the upper injured limb and the patient's health (physical, somatic, mental) was carried out according to the algorithm of comprehensive medical and psychological clinical rehabilitation. As a result of the course of comprehensive medical and psychological clinical rehabilitation, significant positive dynamics was observed, including a decrease in edematous, painful, and inflammatory syndromes. The range of motion in the right upper limb and cervical-thoracic spine increased. Supination and pronation of the right hand became clearer and less painful (from 8 to 2 points), movement in the fingers of the right hand increased and became more steady, a clear pulsation appeared in the area of the skin defect on the right forearm, regression of pain in the elbow and shoulder joints on the right was noted, and the patient began to walk without a mobilization bandage. The course helped to reduce anxiety (from -1.82 to 0.85), asthenic symptoms (from 0.48 to 3.71), obsessive-phobic symptoms (from -1.96 to 1.74), and autonomic disorders (from -0.83 to 2.03). Low cortisol levels (61 nmol/l) in against acute stress indicated the development of post-traumatic stress disorder. Upon completion of the rehabilitation course, cortisol levels rose to a healthy level (246 nmol/l), indicating the effectiveness of the process of restoring the psychophysiological state and adapting to a stressful situation. War trauma is a complex and severe condition that requires an integrated approach to treatment and rehabilitation, covering not only physical but also psychological and social aspects of patients' health.